ANALISIS PENGARUH PEMASARAN PENGALAMAN DAN PERSEPSI NILAI TERHADAP LOYALITAS KONSUMEN, DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN DU CAFE DI SEMARANG - Kartika, Riris Dwi; Yoestini, Yoestini (Diponegoro Journal of Management, 2018)
Du Cafe has decreased sales which can affect the customer loyalty of cafe. Every cafe or restaurant is required to have a different concept so it must have experiential marketing and perceived value, whose main purpose is to influence consumer satisfaction. Building customer satisfaction that will affect on consumer loyalty, so that later will have an impact on sales increase, and can maximize market share in accordance with company expectation.The purpose of this study to analyze experiential marketing and perceived value on customer satisfaction and the impact on customer loyalty. The population of the study was all consumers who had ever done purchase transaction on Du Cafe product at least more than once, where respondents are Semarang people. The samples in this study were 125 respondents. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument.The result show that the experiential marketing has positively and significantly significant   effected   customer   satisfaction,   perceived   value   has   positively   and significantly significant effected customer satisfaction, customer satisfaction has positively and significantly effected customer loyalty, experiential marketing has not significantly effected customer loyalty, and perceived value has positively and significantly significant effected customer loyalty.